Expansion of clinical pharmacist positions through sustainable funding. (1st July 2018) - Moore, Gina D.; Kosirog, Emily R.; Vande Griend, Joseph P.; Freund, Jeff E.; Saseen, Joseph J.
Abstract : Purpose: Expansion of clinical pharmacist positions through sustainable funding is described. Summary: The University of Colorado Skaggs School of Pharmacy and Pharmaceutical Sciences was awarded a 2-year program grant to establish an integrated clinical pharmacy program for underserved residents in family health centers in northeastern Colorado. The grant enabled the hiring of 2 bilingual, full-time, board-certified, postgraduate year 2–trained clinical pharmacists to initiate comprehensive clinical pharmacy services. Clinical pharmacy services for diabetes, hypertension, and dyslipidemia management were provided during direct patient care visits using collaborative drug therapy management protocols to facilitate comprehensive medication management. Initial visits lasted 1 hour, and follow-up visits lasted 30 minutes. In addition, clinical pharmacists provided point-of-care consultations for patients seeing other healthcare providers. All patient encounters and consultations were documented in the electronic health record. Success of the clinical pharmacy program was evaluated based on the achievement of goal blood pressure values, glycosylated hemoglobin values, and low-density-lipoprotein cholesterol levels. Pharmacists' involvement in patient care activities led to improvements in all of these clinical outcomes. This coincided with unique funding opportunities with regional accountable care organizations that sought to demonstrate improved patient care in an expansion population. As a result, 2 grant-funded clinical pharmacist positions in 2 community health clinics were converted into 4 faculty positions in 5 community health centers funded by regional accountable care organizations. Conclusion: Collaboration with accountable care organizations resulted in the successful funding of ambulatory care clinical pharmacy services. These services resulted in improved chronic disease control and provider satisfaction.